Angola : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the oil price shock is adversely impacting the economy of Angola. While oil production has recovered following the completion of maintenance work, non-oil GDP growth is expected to decelerate to 2.1 percent in 2015. The economic situation in 2016 is likely to remain challenging as international oil prices are not expected to recover and risks are on the downside. Growth is projected to remain stable at 3.5 percent in 2016, with the oil sector growing by about 4 percent. The non-oil sector is expected to show a small improvement.